2018
DOI: 10.1177/1478210318774190
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of Australian STEM education strategies

Abstract: In December 2015 the Australian state and territory governments endorsed the ‘National STEM School Education Strategy 2016–2026’. Since then, the individual jurisdictions have released their own STEM education strategies that aim to improve student STEM capabilities and aspirations. This paper analyses the various Australian STEM education strategies in relation to six themes informed by research into effective STEM education: STEM capabilities; STEM dispositions; STEM educational practices; Equity; Trajectori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 34 publications
(36 reference statements)
1
60
0
3
Order By: Relevance
“…Like other teaching and learning strategies, what works best is a mixture of back-and-forth, non-linear combinations of implicit and explicit teaching depending on teachers' professional judgments (p. 204) Given the dwindling numbers of students opting to pursue STEM-related programs and careers in several countries across the globe (see Jones et al, 2018;Marginson et al, 2013;Murphy et al, 2018;Smith & White, 2018), science teachers may need to help students develop a vast array of positive dispositions toward science employing a blended instruction model. Prior research has also demonstrated that such a blended instruction model may lead to better student outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like other teaching and learning strategies, what works best is a mixture of back-and-forth, non-linear combinations of implicit and explicit teaching depending on teachers' professional judgments (p. 204) Given the dwindling numbers of students opting to pursue STEM-related programs and careers in several countries across the globe (see Jones et al, 2018;Marginson et al, 2013;Murphy et al, 2018;Smith & White, 2018), science teachers may need to help students develop a vast array of positive dispositions toward science employing a blended instruction model. Prior research has also demonstrated that such a blended instruction model may lead to better student outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that the number of students choosing to pursue STEM programs and careers has been dwindling over the past few decades in many countries across the world (see Jones et al, 2018;Marginson, Tytler, Freeman, & Roberts, 2013;Murphy, MacDonald, Danaia, & Wang, 2018;Smith & White, 2018). However, building a highly competent, educated, and versatile STEM workforce is crucial for developing and sustaining a global knowledge-based economy (see Freeman, Marginson, & Tytler, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Other countries have implemented similar strategies (e.g., the Netherlands, Belgium, Norway, Ireland, France, Israel, Switzerland, Italy) with centres that aim to improve the quality of STEM teaching and sometimes to increase the popularity of science and technology (Kearney, 2011). A common approach in Australia described by Murphy, MacDonald, Danaia, and Wang (2018) is to establish networks of teachers, teacher trainers and other relevant stakeholders, often at the regional level, with the aim of implementing curricular reform and supporting initiatives favouring inquiry-based learning (e.g., cross-disciplinary, thematic or project work).…”
Section: Challenges For Teaching Stem and Stem Subjects In Rrrmentioning
confidence: 99%
“…Dynamic versatile changes occurring in the modern educational sphere lead the student to adapt to new conditions. Particularly acute is the problem of the effective management of one's own educational activities, achievement of educational independence, initiative and responsibility, finding a rational approach, ensuring high accuracy of educational activities, its productivity, requiring competent implementation of the regulatory and controlling functions, mastering the actions of self-regulation [22][23][24][25][26][27][28][29]. The results of numerous studies in domestic and foreign studies confirm that the quality of the implementation of labor depends on the use of the profession and self-regulation skills of specialists in professional activities [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%